Stimulation of noradrenergic transmission by reboxetine is beneficial for a mouse model of progressive parkinsonism - Kreiner, Grzegorz; Parlato, Rosanna (Scientific reports, 2019)
Parkinson’s disease (PD) is the second most common neurodegenerative disorder and is characterized by motor deficits such as tremor, rigidity and bradykinesia. These symptoms are directly caused by the loss of dopaminergic neurons. However, a wealth of clinical evidence indicates that the dopaminergic system is not the only system affected in PD. Postmortem studies of brains from PD patients have revealed the degeneration of noradrenergic neurons in the locus coeruleus (LC) to the same or even greater extent than that observed in the dopaminergic neurons of substantia nigra (SN) and ventral tegmental area (VTA). Moreover, studies performed on rodent models suggest that enhancement of noradrenergic transmission may attenuate the PD-like phenotype induced by MPTP administration, a neurotoxin-based PD model. The aim of this study was to investigate whether chronic treatment with either of two compounds targeting the noradrenergic system (reboxetine or atipamezole) possess the ability to reduce the progression of a PD-like phenotype in a novel mouse model of progressive dopaminergic neurodegeneration induced by the genetic inhibition of rRNA synthesis in dopaminergic neurons, mimicking a PD-like phenotype. The results showed that reboxetine improved the parkinsonian phenotype associated with delayed progression of SN/VTA dopaminergic neurodegeneration and higher dopamine content in the striatum. Moreover, the alpha1-adrenergic agonist phenylephrine enhanced survival of TH+ neurons in primary cell cultures, supporting the putative neuroprotective effects of noradrenergic stimulation. Our results provide new insights regarding the possible influence of the noradrenergic system on dopaminergic neuron survival and strongly support the hypothesis regarding the neuroprotective role of noradrenaline.